Helium-ion-beam nanofabrication: extreme processes and applications. (23rd November 2020) - He, Shixuan; Tian, Rong; Wu, Wei; Li, Wen-Di; Wang, Deqiang
Abstract: Helium ion beam (HIB) technology plays an important role in the extreme fields of nanofabrication. This paper reviews the latest developments in HIB technology as well as its extreme processing capabilities and widespread applications in nanofabrication. HIB-based nanofabrication includes direct-write milling, ion beam- induced deposition, and direct-write lithography without resist assistance. HIB nanoscale applications have also been evaluated in the areas of integrated circuits, materials sciences, nano-optics, and biological sciences. This review covers four thematic applications of HIB: (1) helium ion microscopy imaging for biological samples and semiconductors; (2) HIB milling and swelling for 2D/3D nanopore fabrication; (3) HIB-induced deposition for nanopillars, nanowires, and 3D nanostructures; (4) additional HIB direct writing for resist, graphene, and plasmonic nanostructures. This paper concludes with a summary of potential future applications and areas of improvement for HIB extreme nanofabrication technology.